PENGARUH GOOD CORPORATE GOVERNANCE, LEVERAGE, ROA, DAN UKURAN PERUSAHAAN TERHADAP TAX AVOIDANCE PADA TAHUN 2011-2013 - Nefita Priamsari, 11.05.52.0131; Kartika, Andi (Students Journal of Accounting and Banking, 2015)
This study aims to determine the effect of corporate governance, leverage, Roa and size Perusahaann against tax avoidance.Â Population in this research are manufacturing companies listed in Indonesia Stock Exchange 2011-2013. The sample in this study were taken by purposive sampling method. Data were analyzed using normality test skwinnes-kurtosis, classic assumption test, koofisiendeterminasi test, F test and test hypotheses.Â The test results In variable Corporate Governance statistically not significant effect on tax avoidance, In the variable Leverage statistically significant negative effect on tax avoidance, In variable Roa statistically significant negative effect on tax avoidance, In variable Company Size statistically significant effect on tax avoidance.Keywords: Corporate Governance, Levarage, Roa, Company Size, Tax Avoidance